Fabrication and characterization of polyurethane foam prepared from liquefied oil palm mesocarp fibre with renewable monomer made from waste cooking oil - M. Rus, A. Z.; Kormin, S. (African Journal Online (AJOL), 2018)
This study aims performance characteristics of polyurethane foams prepared by the reaction of biopolyol prepared from liquefied oil palm mesocarp fibre and renewable monomer with methylene diphenyl diisocyanate. The effect of prepared oil palm mesocarp biopolyol with incorporation of renewable monomer of PU foam on the thermal stability, mechanical properties and was analyzed by thermo gravimetric analysis, tensile and compressive tests and Fourier transform infrared spectroscopy. The improved thermal properties were achieved at a composition of oil palm mesocarp fibre foams (PMF). Oil PMF foams showed mechanical strength as compared to renewable monomer foams. PU foam prepared from oil palm mesocarp biopolyol with incorporation of renewable monomer improved the foams strength. An infrared spectroscopy study demonstrated the formation of urethane linkage.